Analysis of Factors Influencing Students' Interest in Sports at Public Junior High School 5 Kodi Balaghar Southwest Sumba - Mete, Noprianus; Saputro, Yulianto Dwi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the factors influencing students' interest in sports at SMP Negeri 5 Kodi Balaghar, Southwest Sumba. This research is descriptive and uses primary data obtained through questionnaires and measured using the Linkert scale. The population and sample in this study were 230 students at SMP Negeri 5 Kodi Balaghar, Southwest Sumba. At SMP Negeri 5 Kodi Balaghar, Southwest Sumba, interest in sports is still low. Therefore, efforts are needed to determine student interest in order to improve achievement in this area. The data analysis technique used was descriptive statistical analysis, with data presented in tables. The results showed that students' interest in sports was influenced by the enjoyment or interest factor, which scored 75.8% (strong category), the attention factor at 92.7% (very strong category), and the need factor at 76.3% (strong category).